Comparative clinicopathological study of the main anatomic locations of oral squamous cell carcinoma - Amezaga‐Fernandez, Iñaut; Aguirre‐Urizar, José Manuel; Suárez‐Peñaranda, José Manuel; Chamorro‐Petronacci, Cintia; Lafuente‐Ibáñez de Mendoza, Irene; Marichalar‐Mendia, Xabier; Somoza‐Martín, José Manuel; Blanco‐Carrión, Andrés; Antúnez‐López, José; García‐García, Abel (Oral diseases, 2024)
Objective To analyze the clinicopathological and evolutionary profile of the main locations of oral squamous cell carcinoma (OSCC). Materials and Methods This is a retrospective study on 133 patients treated for OSCC. The group was composed of 48 women and 85 men, with a mean age 63.9 ± 12.73 years. Most cases involved the lingual border of tongue (63), followed by the gingiva (36) and the floor of mouth (34). A comparative analysis was performed using multinomial regression. Results There were significant differences regarding age, sex, tobacco and alcohol consumption, liver pathology, oral potentially malignant disorders, and bone and perineural invasion. In multivariate regression, tobacco consumption, and bone invasion remained significant. There were no significant differences in relation to prognosis. Conclusion The location of OSCC is an important factor in the clinicopathological assessment of this neoplasm. The main locations of OSCC show differential etiopathogenic and clinicopathological aspects. Tobacco consumption has a great relevance in the floor of mouth; nonetheless, it is less important in the tongue border and the gum, which suggests other pathogenic factors. It is necessary to consider the anatomical location of OSCC in preventive protocols, with the aim of reducing its high mortality.